Glosa do uchwały Sądu Najwyższego z dnia 15 grudnia 2005 r., sygn. I KZP 34/05: OSNKW 2006, nr 1, poz. 2 - Wróbel, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
It must be assumed that the point of view of the Supreme Court, as presented in the said judgement, that the subject of protection of Art. 220 of the Polish Criminal Code is the safe and hygienic working environment as an employee’s right is correct — an employee understood here as a subject of employment relationship specifi ed in Art. 22 § 1 of the Polish Labour Code. This applies to the following types of employment relationships: contract of employment, two types of appointment, election, cooperative contract of employment Art. 2 of the Labour Code. It should be emphasised that the subject of protection of Art. 220 of the Criminal Code is not employee’s right to safe and hygienic working environment but also life and health of an employee in the work process, as well as safe and hygienic working environment itself.
Keywords: glosa; uchwała Sądu Najwyższego - sygn. I KZP 34/05